The influence of AC and Ni/AC catalyst in the antioxidant additives production from argan shells lignin - Afailal, Zainab; Gil-lalaguna, Noemí; Vanzella, Andrea; Arauzo, Jesus; Sanchez, Jose Luis (Jornada de Jóvenes Investigadores del I3A, 2022)
In this work, the production of antioxidant additives via hydrothermal treatment of lignin from argan nutshells (agricultural waste) was evaluated. Specifically, the effect of using a catalyst supported on activated carbon which had been prepared from the same waste (argan nutshells) has been studied.